Thailand : Adjusting to Success: Current Policy Issues - Robinson, David (Occasional Papers; Occasional Paper ;, 1991)
Thailand's sucess with economic development in recent decades is due mainly to is commitment to an outward-looking, market-based economy, a development strategy centered on the private sector, and cautious financial policies. This papers dicusses recent economic strains and how the authorities are coping with them to sustain the momentum of development.